Immunomodulatory roles of butyrate in asthma: mechanisms and therapeutic potentials - Liu, Chao; Zeng, Zhu; Chen, Mei; Fan, Yuwei; Huang, Qingsong; Wu, Jianying (Frontiers in Immunology, 2025)
Asthma, a chronic airway inflammatory disease driven by complex immune dysregulation, still remains a global health challenge despite its advances in biologic therapies. Butyrate, a major short-chain fatty acids (SCFAs) produced by intestinal microorganisms in the fermentation of dietary fiber, has recently garnered considerable attention for its multifaceted roles in maintaining immune homeostasis and modulating airway inflammation. This review summarizes the molecular mechanisms and recent advances by which butyrate alleviates asthmatic inflammation, including suppression of excessive activation of type 2 innate lymphoid cells (ILC2s) and T helper 2 (Th2) cells, inhibition of mast cells (MCs) degranulation, epigenetic modulation, regulation of receptor-mediated signaling pathways, and interactions along the gut–lung axis. We integrate current knowledge of butyrate’s multidimensional immunoregulatory network in asthma and propose a dual approach—via microbiota-based interventions and targeted modulation of the immune microenvironment—to potentially overcome the limitations of conventional corticosteroid therapies. Despite its promising prospects, its clinical translation still faces many challenges, especially in airway specific delivery, improved bioavailability, and long-term safety. Innovative strategies, including nano-carrier engineering and targeted probiotic preparations are expected to improve their bioavailability and tissue specificity. Future research should focus on clarifying the dose-response relationship, long-term safety, and establishing individualized treatment stratification based on patients’ microbiota-metabolic characteristics.